Eating And Handwashing Habits Of Community Before and During The Covid 19 Pandemic In Jayapura City - Yulia Nuradha Wasaraka (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan Pelamonia, 2023)
Introduction : The global pandemic caused by Covid 19 is inflicting community concerns. It appears on the community’s health and health behavior change. The concern of corona virus infections will impact on community’s eating and handwashing habits to avoid the infections. Purpose : To know the description of eating and handwashing habits of community before and during the Covid 19 pandemic in Jayapura City. Methods : This type of research is descriptive observational. The subject of this research is community of Jayapura City 17-55 years old, and have an android mobile. Respondents of this research is 123 people. Data of this research was collected in 2020. Results : Respondents’ breakfast habits is increasing from 41% to 52%. Frequency of eating 3 times a day is increasing from 42% to 45%. Most of the respondents consuming vegetable protein 4-8 pieces a day before Covid 19 pandemic (35%) and 1-3 pieces a day during Covid 19 pandemic (43%). Most of the respondents consuming animal protein 2-4 pieces a day before Covid 19 pandemic (48%) and during Covid 19 pandemic (54%). Most of the respondents consuming vegetables less than 3 bowl a day before Covid 19 pandemic (58%) and during Covid 19 pandemic (53%). Most of the respondents rarely consume fruits before Covid 19 pandemic (38%) and consuming fruits 1-3 pieces a day during Covid 19 pandemic (33%). Before and during the pandemic, most of the respondents consuming karbohidrat 1-2 plates a day. Respondents’ habits of taking supplements is increasing from 15% to 35%. Respondents’ habits of handwashing is increasing from 49% to 93%. Respondents’ habits of washing hands 6 steps as recommended by WHO is increasing from 39% to 83%. Respondents’ habits of washing hands with soap is increasing from 54% to 94%. Respondents’ habits of washing hands after going out is increasing from 36% to 89%. Conclusion : There was a change on eating and handwashing habits of community before and during the Covid 19 pandemic. Keyword : Covid 19 pandemic, eating habits, handwashing habits